2022
DOI: 10.3390/cancers14071638
|View full text |Cite
|
Sign up to set email alerts
|

Tumor BRCA Testing in Epithelial Ovarian Cancers: Past and Future—Five-Years’ Single-Institution Experience of 762 Consecutive Patients

Abstract: The establishment of PARP inhibitors in the treatment of epithelial ovarian carcinoma (EOC) has prompt BRCA assessment at the time of diagnosis. We described our five years of experience of tumor BRCA testing, as part of a multidisciplinary workflow for the management of EOC patients. We used a BRCA next-generation sequencing (NGS) test for profiling formalin-fixed, paraffin-embedded (FFPE) EOCs of 762 consecutive patients, with a success rate of 99.7% and a median turnaround time of 12 days. We found 178 (23.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 49 publications
(70 reference statements)
0
3
0
Order By: Relevance
“…95 cases underwent DNA extraction,obtaining a median concentration of 38.6 ng/μl (range 1.1-99.7 ng/μl).In 84 cases (88.4%) DNA was extracted from surgical specimens, while in 11 cases (11.6%) DNA was extracted from biopsies.15 of 95 (15.8%) samples, including 5 biopsies and 10 surgical specimens, were not adequate for analysis with AmoyDx HRD Focus panel due to the low DNA yield and were addressed to tumor BRCA test assessment only, as previously reported 17 . The remaining 80 (84.2%) samples were subjected to HRD testing, giving a result in all the cases.…”
Section: Resultsmentioning
confidence: 99%
“…95 cases underwent DNA extraction,obtaining a median concentration of 38.6 ng/μl (range 1.1-99.7 ng/μl).In 84 cases (88.4%) DNA was extracted from surgical specimens, while in 11 cases (11.6%) DNA was extracted from biopsies.15 of 95 (15.8%) samples, including 5 biopsies and 10 surgical specimens, were not adequate for analysis with AmoyDx HRD Focus panel due to the low DNA yield and were addressed to tumor BRCA test assessment only, as previously reported 17 . The remaining 80 (84.2%) samples were subjected to HRD testing, giving a result in all the cases.…”
Section: Resultsmentioning
confidence: 99%
“…Most of the BRCA alterations are germline pathogenic mutations, but in 30% of the cases, the alterations can only be seen at the somatic level; therefore, HGSOC patients can benefit from tumor tissue DNA testing for s BRCA mutations. In general, in 13–23% of the diagnostic histological samples from HGSOC patients, a pathogenic BRCA1 or BRCA2 gene variant can be found [ 43 , 44 ]. In the AGO TR 1 study, 6.3% of the included ovarian cancer patients had somatic BRCA1/2 gene mutations [ 45 ], while the FLABRA study showed a higher than estimated rate of tumor BRCA mutations in ovarian cancer patients in a Latin American population of 28%, without specifying whether it was at the germline or somatic level [ 46 ].…”
Section: Ovarian Cancermentioning
confidence: 99%
“…PARPis have received FDA-approval for the treatment of HGSOC patients with BRCA1 or BRCA2 alteration (germline and/or somatic), following response to first-line platinum-based chemotherapy [ 13 ]. According to various studies, around 16–23% of the HGSOC samples harbor a pathogenic variant on BRCA1 or BRCA2 at the time of diagnosis [ 14 , 15 , 16 ]. While the majority of these alterations can be detected at the germline level in patients with hereditary breast and ovarian cancer syndrome, almost 30% of these changes occur in the tumor itself and can only be identified at the somatic level [ 17 ].…”
Section: Introductionmentioning
confidence: 99%